Current status and perspectives of the quality system in histocompatibility laboratories in Poland - Uhrynowska-Tyszkiewicz, Izabela; Bogunia-Kubik, Katarzyna; Baj-Krzyworzeka, Monika; Piątosa, Barbara (Frontiers in Genetics, 2024)
Allogeneic transplantation is a multi-step process involving many clinicians and laboratory personnel working together to achieve a common goal -to maximize the recipients' chance of survival and to improve their quality of life. One of the key elements of the process is to ensure high quality, accuracy, and reliability of histocompatibility testing. This manuscript presents:(1) the development and organizational principles of the national system of supervision and control of histocompatibility laboratories in Poland, (2) proficiency testing schemes, (3) problems faced by these laboratories, as well as (4) suggestions and prospects for the future raised by members of the Polish histocompatibility community